Optimizing Student Management to Improve Educational Service Quality: A Qualitative Case Study in Integrated Islamic Elementary Schools - Mayasari, Annisa; Arifudin, Opan; Herawati, Silvi; Rosanti, Atik; Agung Prayogi, Rachmad (LP. Ma'arif Janggan Magetan, 2024)
This study examines how the quality of educational services can be improved through the optimization of student management implementation. The research was conducted at an Integrated Islamic Elementary School in Bandung. The study aims to provide a comprehensive description and practical recommendations for school stakeholders regarding the effective implementation of student management activities to enhance the quality of educational services. A qualitative research approach was employed, utilizing field observations, structured interviews with school staff and students, and document analysis as primary data collection techniques. The findings indicate that optimal implementation of student management is achieved through the systematic execution of four main activities: planning, guidance, evaluation, and student transfer. These activities are most effective when supported by adequate school facilities and infrastructure, strong leadership from the school principal, and collaborative efforts among teachers, educational staff, students, and the school committee. The study contributes theoretically by providing a structured framework for understanding the relationship between student management practices and educational service quality. Practically, it offers actionable guidance for schools seeking to optimize student management processes and improve overall educational outcomes.